PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI PADA POS BADAN SAR NASIONAL (BASARNAS) SIBOLGA/TAPANULI TENGAH - Elinatantri Sinaga; Rosmita Ambarita; Nur Ainun Hasibuan (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine the effect of Occupational Safety and Health on Employee Productivity either partially or simultaneously. The research method used in this study was quantitative research. This research was conducted on a sample of 30 employees at the Sibolga/Tapanuli Tengah Sarnas Agency Post. From the results of the t-test for the Occupational Safety variable, the t-count value is 8.478 while the t-table distribution value is 0.01 (10%) of 1.31370, so t count> t table and a significance value of 0.000 <0.10 means the independent variable Occupational Safety (X1) has a positive and significant effect on employee productivity. The t-test results for the Occupational Health variable, the t-count value is 6.185 while the t-table distribution value is 0.01 (10%) of 1.31370, so t count> t table and a significance value of 0.000 <0.10. The f-test results show a calculated f value of 129.470. After that it is compared with the f table value of 3.34 with a significant 10% (0.1). So it can be concluded that f count > f table (129.470 > 3.34 with Sig f 0.000 <0.1) this means that the independent variables Safety (X1) and Occupational Health (X2) together have a positive and significant effect on Employee Productivity. This means that the independent variable Occupational Safety and Health has a positive effect simultaneously on employee productivity.